2022
DOI: 10.1101/2022.11.15.516655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychedelic compounds directly excite 5-HT2ALayer 5 Pyramidal Neurons in the Prefrontal Cortex through a 5-HT2AGq -mediated activation mechanism

Abstract: Psilocin, the active compound in Psilocybe sp. mushrooms, is a serotonergic psychedelic that has recently gained renewed interest due to its potential as a therapeutic tool. Despite promising clinical findings, the underlying signaling mechanisms and brain region-specific effects of psilocin and other psychedelic drugs remain unclear. Psilocin, like other psychedelic compounds, is an agonist at many serotonin and other biogenic amine receptors; however, activation of serotonin (5-Hydroxytryptamine, or 5-HT) 2A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
1
7
1
Order By: Relevance
“…These findings are important because of a recent report suggesting that many HTR2A agonists may exert their actions via intracellular rather than plasma membrane receptors (Vargas et al, 2023). As we recently reported (Schmitz et al, 2022), psychedelic drugs increase the firing of genetically-identified HTR2A neurons in a manner similar to that reported here for 5-HT. As 5-HT is extracellularly applied, our results are consistent with the hypothesis that the psychedelic actions of HTR2A agonists are mediated by direct actions of pyramidal neuron firing via surface HTR2A receptors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are important because of a recent report suggesting that many HTR2A agonists may exert their actions via intracellular rather than plasma membrane receptors (Vargas et al, 2023). As we recently reported (Schmitz et al, 2022), psychedelic drugs increase the firing of genetically-identified HTR2A neurons in a manner similar to that reported here for 5-HT. As 5-HT is extracellularly applied, our results are consistent with the hypothesis that the psychedelic actions of HTR2A agonists are mediated by direct actions of pyramidal neuron firing via surface HTR2A receptors.…”
Section: Discussionsupporting
confidence: 87%
“…Series resistance was continuously monitored with a hyperpolarizing 10 mV pulse; cells with axis resistance >20 MΩ were excluded from the data set. HTR2A expressing neurons were identified via tdTomato expression using fluorescent optics and brief (<2 sec) episodic illumination as previously described (Schmitz et al, 2022). During voltage clamp recording (V hold = −70mV), electrophysiological properties of cells were determined by pClamp 10 Clampex software using a 10 mV pulse delivered after breaking the cellular membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Although psychedelics do enhance some forms of neuronal excitability, these data indicate that the dominant and net effect is dose-dependent suppression of intrinsic excitability, necessitating a revision of the current paradigm ( 1924 ). Our acute results differ from some previous studies that concluded that psychedelics increase intrinsic excitability, likely due to prior studies examining RMP changes or using only near-threshold current injections, which fail to reveal the larger intrinsic suppression changes ( 37 , 38 , 40 , 42 ). Additionally, we utilized psychedelic drugs ( 4750 , 7276 ), in contrast to many former studies that used 5-HT2AR agonists with non- or unknown psychedelic effects such as serotonin or alpha-methyl-serotonin ( 7784 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Apart from neuromodulation [95,[128][129][130][131][132], serotonin has potent vasoactive effects [44,45,133]. For example, serotonin binding triggers vasoconstriction through intracellular signaling pathways involving phospholipase C, calcium release, and protein kinase C phosphorylation [134].…”
Section: 23) Neurovascular Couplingmentioning
confidence: 99%